Концепція «глибинного спілкування» Г. Батищева та її дидактично-освітні імплікації - Ганаба, Світлана; Ganaba, Svitlana (Східноєвропейський національний університет імені Лесі Українки, 2013)
Статтю присвячено проблемі епістемологічного й аксіологічного потенціалів категорій концепції «гли-бинного спілкування» Генріха Батищева в практиці дидактично-освітньої діяльності. Наголошено, що гли-бинне спілкування – це онтологічний процес спів-буттєвості, у якому людина виявляє здатність долучитися до внутрішнього світу іншої людини. Досвід іншого дає змогу подивитися на світ очима іншого та на себе очима іншого. The article observes the problems of epistemological and axiological categories in Henry Batishchev’s conception about «profound communication» and using it in practice of didactic-educational activity. The author wanted to stress, that «profound communication» is the ontological process of co-existence where a person able to be admitted to the inner world of another person. Thus, the experience of the another permits to look at the same things from the different point of view and to see yourself from the other side. The author stresses that a person, by his nature, is a dialogical creature, but there is a difference between «communication» is used for informative link, but «dialogue» means a personal connection between subjects. The «dialogue» is explained as accessibility to another person accessibility to your self. Involving the person in the process of active discovering the universe, having skills to transform this information in useful knowledge are the meaningful ideas of «profound communication» in education. This article touches the questions of didactic-educational methods introduction which are based on inter-subject co-operation.
Batishchev’s Conception of «Profound Communication» and it’s Didactic-Educational Implications
Keywords: глибинне спілкування; profound communication; діалог; dialogue; співпричетність; correlation; освіта; education; творчість; creativity